United Arab Emirates : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision and Payment Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper presents key findings of the Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, and Payment Systems for the United Arab Emirates (UAE). The UAEs financial sector and financial sector supervision are developing unevenly. The financial sector is dominated by well-supervised banks, which pose minimal near-term systemic risk. Although the payment systems are simple and far from state-of-the-art, they are well managed, and systemic risks are limited.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet